algebra

solve by substitution

3x-y = -7
x+y = -9

Substitute 3x+7 for y in the second equation, and solve the resulting equation for x.

  1. 👍 0
  2. 👎 0
  3. 👁 50
asked by Tony

Respond to this Question

First Name

Your Response

Similar Questions

  1. Algebra 1

    What is an equation of a line perpendicular to the line with equation y = 1 - 3x a.y=-3x + 5 b. y=3x + 5 c.y=-1/3x + 5 d. y=1/3x + 5 To solve the linear system below, which substitution of unkowns is proper ? x + 4y= -6 5x - 3y =

    asked by Ley on April 22, 2013
  2. ALGEBRA 1!PLZ HELP!

    Use the Substitution method to solve the system of equations. y - 2x = -5 3y - x = 5 Solve the first equation for y. y = 2x-5 Substitute that for y in the second equation and solve for x. Then use the value of x to substitute back

    asked by SANDRO! on November 6, 2006
  3. algebra

    use substitution to solve the linear system 3x+2y=-5 4x-3y=16 help plz!!! Solve for y in one formula, and then substitute that value for y in the other formula to solve for x. Once you find x, substitute that value into either

    asked by kerry on March 7, 2007
  4. algebra

    use substitution to solve the linear system 3x-y=15 x+2y=-2 Solve for y in one formula, and then substitute that value for y in the other formula to solve for x. Once you find x, substitute that value into either formula to get

    asked by lisa on March 7, 2007
  5. How do I do this.?(Math.)

    Use the Substitution method to solve the system of equations. y - 2x = -5 3y - x = 5 Solve one of the equations for x or y. Let's solve the first one for y: y - 2x = -5 y = 2x - 5 Now let's substitute 2x - 5 for y in the second

    asked by Margie on February 5, 2007
  6. algebra

    5x-2y=-5 y-5x=3 substitution Substitute 5x +3 for y in the first equation, then solve it for x. Substitute 5x +3 for y in the first equation, then solve it for x. When I subsitute 5x+3 into the equation I get x=1/5 and y=2 is this

    asked by Tony on March 20, 2007
  7. math

    Solve systems by substitution 5x - 2y = -5 y - 5x = 3 Substitute 5x + 3 for y in the first equation, and solve it for x. Once you have x, use either of the two equations you wrote to solve for y.

    asked by Robin on August 8, 2007
  8. algebra 1

    Solve the Foll by substitution x=1/5y 3x+2y=26 So, substitute 1/5y for x in the second equation. Then solve for y. Can you take it from here? yes thanks I figured it out. Danielle

    asked by DANIELLE on December 21, 2006
  9. Math

    Solve the system by addition or substitution. 3x – 4y = 8 6x – 2y = 10 Please get me on the correct track for 3x -4y =8 x=4, y=1 for 6x - 2y =10 x= 2, y= 1 Solve one equation for x. 3x = 4y + 8 x = (4y + 8)/3 Insert that value

    asked by Amanda on May 20, 2007
  10. Algebra 1

    bobpursey, In this problem you helped me with earlier: Solve using any appropriate method. y = 2× - 5, y = ½× + 1 Substitution, substitute for y. 2×-5=½ × + 1 3/2 x=6 x=4 y= 2*4-5=3 How did you choose which method you were

    asked by slomo on January 3, 2015
  11. Pre-Calculus

    If you solve the following system of equations by substitution, which statement is true? x = z x - 2y + z = 6 2x + y - 2z = 1 A. You can substitute z for x into the second and third equations. B. You can substitute x for z into

    asked by Caroline on January 22, 2013

More Similar Questions